Anti-ulcer Potential of Aqueous and Ethanolic Bark Extracts of â€œSaraca indicaâ€ Using Different Screening Models - Venu, Dr. Kola (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: Saraca indica (Cesalpiniaceae) is a plant, reported for its variety of ethnic medicinal uses, and widely grown in Asia, Africa, and the Caribbean for its edible bark. The present work has been planned to screen the antiulcer activity of bark of the plant with the ethanolic and aqueous extracts. Materials and Methods: Bark powder was successively extracted with ethanol (95%) and water using Soxhlet extraction and subjected to phytochemical screening to identify different phytoconstituents. Ld50 studies for both (ethanolic and aqueous) extracts were conducted up to the dose level of 2 g/kg by following OECD up-and-down method of guidelines No.425. The antiarthritic activity was performed using pylorus ligation, aspirin, and stress-induced ulcer models in rats. Statistical analysis was performed using one-way analysis of variance (ANOVA) followed by Dunnett’s test. P < 0.05 was considered statistically significant. Results: Preliminary phytochemical studies revealed the presence of saponins, sterols, mucilage, glycosides, and alkaloids, steroidal saponins in both the ethanolic and aqueous extracts of S. indica. No mortality was observed with aqueous and ethanolic extracts up to the maximum dose level of 2 g/kg. Both the extracts except with low dose 100 mg/kg other two doses, that is, medium and high have significantly reduced the ulcer number (0.83 ± 0.0.16, 1.5 ± 0.34 and 0.50 ± 0.11, 0.66 ± 0.21), ulcer score (1.5 ± 0.12, 1.66 ± 0.16 and 0.83 ± 0.10, 0.91 ± 0.15), and ulcer index (13.64, 9.80 and 11.20, 8.25), and a significantly ulcer inhibition (41.10%, 27.30% and 68.76%, 54.25%) is noted. Conclusion: From the present experimental findings of both pharmacological and biochemical parameters observed from the current investigation, it is concluded that the doses of 200 mg/kg and 400 mg/kg aqueous extract of S. indica possess potentially useful anti-ulcer activity since it gives a positive result in ulcer score and ulcer index and a significant ulcer inhibition.